2018
DOI: 10.1371/journal.pone.0210087
|View full text |Cite
|
Sign up to set email alerts
|

Identification of suitable reference genes for real-time qPCR in homocysteine-treated human umbilical vein endothelial cells

Abstract: The imbalance in homocysteine (Hcy) metabolism has been implicated in the pathogenesis of human diseases, including cardiovascular and neurodegenerative disorders. When attempting to identify gene expression profiles using quantitative real-time reverse transcription polymerase chain reaction (RT-qPCR), the selection of suitable reference genes is important. Here, the expression levels of 10 commonly used reference genes were assessed for normalization of RT-qPCR in Hcy-treated human umbilical vein endothelial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 40 publications
0
9
0
Order By: Relevance
“…As suggested by Andersen et al 66 , a minimum of 5 candidates reference genes should be analysed. miR-16-5p, miR-103a-3p and miR-191-5p were chosen because of their reported expression in BM-MSCs 23 or their use in stability analysis in other models [67][68][69][70] . miR-21-5p was chosen for validation experiment since it is described to be expressed in BM-MSCs and could be used as BM-MSC marker 23 .…”
Section: Methodsmentioning
confidence: 99%
“…As suggested by Andersen et al 66 , a minimum of 5 candidates reference genes should be analysed. miR-16-5p, miR-103a-3p and miR-191-5p were chosen because of their reported expression in BM-MSCs 23 or their use in stability analysis in other models [67][68][69][70] . miR-21-5p was chosen for validation experiment since it is described to be expressed in BM-MSCs and could be used as BM-MSC marker 23 .…”
Section: Methodsmentioning
confidence: 99%
“…For example, statin-treated HUVEC cells showed that HPRT1 and YWHAZ were considered the most suitable reference genes 29 . However, in homocysteine-treated HUVEC cells, YWHAZ was not stably expressed and ranked seven of eight 21 . In addition, hydrogen peroxide-treated HUVEC showed HPRT1 was a less reliable reference gene with a ranking of 11 of 15 20 .…”
Section: Discussionmentioning
confidence: 98%
“…Multiple studies have investigated candidate reference genes in iPSCs or ECs 10,19−23 , during reprogramming and differentiation 10,23 . In addition, various publications reported a selection of housekeeping genes in endothelial cells, such as microvascular EC 19 , human retinal EC 21 , and human blood-brain barrier EC 22 . The candidate reference genes examined in these studies were among the commonly used housekeeping genes in our study, including B2M, GAPDH, GUSB, HPRT1, HMBS, and YWHAZ.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple studies have investigated candidate reference genes in iPSCs or ECs 18 , 29 33 , during reprogramming and differentiation 18 , 33 . In addition, various publications reported a selection of housekeeping genes in endothelial cells, such as microvascular EC 29 , human retinal EC 31 , and human blood–brain barrier EC 32 . The candidate reference genes examined in these studies were among the commonly used housekeeping genes in our study, including B2M , GAPDH , GUSB , HPRT1 , HMBS , and YWHAZ .…”
Section: Discussionmentioning
confidence: 99%